Analisis Pengelolaan Badan Usaha Milik Desa (Bumdes) Aeeropa Di Desa Air Paoh Kecamatan Baturaja Timur Kabupaten Ogan Komering Ulu - Eva Susanti; Aprilia Lestari (UNIVERSITAS INDO GLOBAL MANDIRI, 2020)
Village is a government that is given the right of autonomy which makes it as s a legal entity that has the right to regulate and manage the affairs of the local community. Therefore, the existence of villages both as a government agency and a legal entity unit are very important and strategic. One of the greatest economic strengths of villages for development, establishment, and community empowerment is the funds provided by the government for the management of Village-Owned Enterprises (BUMDes). This qualitative study used descriptive design. From the research results, it was obtained that the management of BUMDes Aerropa has not run well. Management has not yet achieved the objectives of BUMDes, Aeeropa has so far only been used as a complement to village organizers. This was influenced by many factors such as the condition of resources, both human, financial, and natural resources that were less qualified, the absence of the role of the community in the formation and development of Aeeropa as BUMDes and the lack of local government support, and also the absence of cooperation with third parties. Keywords : management, village, Village-Owned Enterprises (BUMDes)